Physician-leaders and hospital performance: Is there an association? - Amanda H. Goodall (Institute for the Study of Labor (IZA), 2011)
Although it has long been conjectured that having physicians in leadership positions is valuable for hospital performance, there is no published empirical work on the hypothesis. This cross-sectional study reports the first evidence. Data are collected on the top-100 U.S. hospitals in 2009, as identified by a widely-used media-generated ranking of quality, in three specialties: Cancer, Digestive Disorders, and Heart and Heart Surgery. The personal histories of the 300 chief executive officers of these hospitals are then traced by hand. The CEOs are classified into physicians and non-physician managers. The paper finds a strong positive association between the ranked quality of a hospital and whether the CEO is a physician (p<0.001). This kind of cross-sectional evidence does not establish that physician-leaders outperform professional managers, but it is consistent with such claims and suggests that this area is now an important one for systematic future research.
urn:nbn:de:101:1-201107133439
Keywords: I19; M12; M51; 330; organizational performance; expert leaders; hospitals; physicians; professional managers